2022
DOI: 10.3390/polym14183851
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Dynamics Simulation of Polymers’ Interactions with Kaolinite (010) Surfaces in Saline Solutions

Abstract: The search for polymers that meet the demands of the water recovery process in mining is a contingent challenge. Both the presence of clays and saline waters can impair water recovery from tailings when conventional flocculants are used. In this work, the adsorption of polyacrylamide (PAM), hydrolyzed polyacrylamide (HPAM), poly(2-acrylamido-2-methyl-1-propane sulfonic acid) (PAMPS), polyacrylic acid (PAA), polyethylene oxide (PEO), and guar gum (GUAR) on a kaolinite surface (010) was investigated using classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Molecular dynamics (MD) simulation has become a complementary method to experimental studies to investigate the microscopic mechanisms of clay–polymer interactions . In recent years, many MD researches of the clay–polymer composites have been conducted including the mostly used polymer types for the organo-modified engineering clay barriers, such as poly­(acrylic acid) (PAA), polyacrylamide (PAM), poly­(ethylene oxide) (PEO), , polyethylene glycol (PEG), , poly­(vinyl alcohol) (PVA), poly­(dimethysiloxane) (PDMS), chitosan, polycarboxylate, polycaprolactone (PCL), cellulose acetate (CA), guar gum, and xanthan gum, as summarized in Table . The main adsorption mechanisms between clay and polymer were substantiated to be (1) cation bridges between the negative clay surface and oxygen containing functional groups of polymers (such as carboxyl); (2) hydrogen bond between the clay surface oxygens and hydroxyls or amidogens of polymers; and (3) electrostatic attraction between the negative clay surface and positive functional groups of polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics (MD) simulation has become a complementary method to experimental studies to investigate the microscopic mechanisms of clay–polymer interactions . In recent years, many MD researches of the clay–polymer composites have been conducted including the mostly used polymer types for the organo-modified engineering clay barriers, such as poly­(acrylic acid) (PAA), polyacrylamide (PAM), poly­(ethylene oxide) (PEO), , polyethylene glycol (PEG), , poly­(vinyl alcohol) (PVA), poly­(dimethysiloxane) (PDMS), chitosan, polycarboxylate, polycaprolactone (PCL), cellulose acetate (CA), guar gum, and xanthan gum, as summarized in Table . The main adsorption mechanisms between clay and polymer were substantiated to be (1) cation bridges between the negative clay surface and oxygen containing functional groups of polymers (such as carboxyl); (2) hydrogen bond between the clay surface oxygens and hydroxyls or amidogens of polymers; and (3) electrostatic attraction between the negative clay surface and positive functional groups of polymers.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the research on the structure, hydrodynamic radius, and shape anisotropy of PEO has been completed by molecular dynamics simulation [27,28]. Regarding the research on the microscopic adsorption mechanism of PEO on mineral surfaces, Lee et al, found that the adsorption of PEO on the hydrophobic interface of minerals produced a transition process from mushroom morphology to brush morphology [29], and PEO was easily adsorbed on the edge surface with high hydroxyl content [30]. At present, there are few studies on the anisotropic adsorption of PEO and kaolinite.…”
Section: Introductionmentioning
confidence: 99%